Self-assessment of Information and Communication Technology (ICT) Competence Needs Among Student-Teachers Using UNESCO ICT-CFT in Colleges of Education in North Central, Nigeria - Onuyi, Anaza, Abdulmumuni (Journal of Education and Practice, 2021)
Purpose: The objective for the study was using the fourth level of UNESCO ICT-CFT on the technology literacy approach to determine student-teachers' self-assessment of ICT competency needs in colleges of education. Methodology: The study adopted the descriptive research of cross-sectional survey type. Three research questions and two hypotheses were drawn. A total of 1,211 student-teachers were randomly selected from 11 colleges of education in North-central, Nigeria. Data were collected through administration of validated questionnaire adapted from UNESCO ICT-CFT. Mean was used to answer the research questions 1-3 while t-test and Kruskal Wallis were used to test hypotheses one and two respectively. Findings: The result revealed that based on the fourth level of the Technology Literacy approaches of UNESCO ICT-CFT, student-teachers in the colleges of education have high ICT competence needs; there was a significant difference among male and female student-teachers ICT competence needs in ICT integration; also, there was significant differences in area of specialization of student-teachers ICT competence needs in ICT integration. Unique contribution to theory, practice and policy: The study therefore recommended that government in collaboration with private sector should provide student-teachers with the required ICT needs to be at par with their counterpart from other parts of the world; government and authorities of colleges of education should take into consideration female student-teachers while planning to integrate ICT in colleges of education and in procurement of ICT facilities; and student-teachers area of specialization should be taken into consideration during the purchase of ICT facilities for student-teachers use in colleges of education. Key Words: Self-assessment, ICT, ICT Competence Needs, UNESCO ICT-CFT, Colleges of education.